Microbial flora surrounding orthodontic temporary skeletal anchorage devices: A systematic review - Navia Jose Paul; Haritha Pottipalli Sathyanarayana; Vignesh Kailasam (Journal of Oral Biology and Craniofacial Research)
Aim: The oral cavity harbours distinct microorganisms, which create a unique microenvironment. These microorganisms might trigger inflammatory reactions in the host, potentially leading to inflammation that can question the stability of temporary skeletal anchorage devices(TSADs). This study aimed to systematically review the literature on the type of microorganisms around TSADs. Methods: A search of studies in six electronic databases – Cochrane Library, PubMed, OVID, Scopus, LILACS and Web of Science were performed until 30 May 2024 without any restriction in date or language of publication. The selection of articles was limited to studies evaluating the microorganisms around TSADs during orthodontic treatment. Two reviewers independently performed eligibility screening, study selection, and data extraction. The Newcastle Ottawa scale was used to assess the Risk of bias in all the included studies. Meta-analysis could not be performed because of the heterogeneity of the studies. Results: From 7020 articles, seven prospective studies were included for the qualitative analysis. Porphyromonas gingivalis and Treponema denticola were found around all TSADs used in orthodontic therapy. There was a significant difference in the type of microorganisms around successful and failed TSADs. Conclusions: There was an overall colonization of diverse microorganisms around TSADS. Failed TSADs showed greater Porphyromonas gingivalis, Parvimonas micra and facultative anaerobic enteric commensal Enterobacter.